Direct Observation of Phagocytosis and NET-formation by Neutrophils in Infected Lungs using 2-photon Microscopy - Hasenberg, Mike (MyJove Corporation, 2011)
After the gastrointestinal tract, the lung is the second largest surface for interaction between the vertebrate body and the environment. Here, an effective gas exchange must be maintained, while at the same time avoiding infection by the multiple pathogens that are inhaled during normal breathing. To achieve this, a superb set of defense strategies combining humoral and cellular immune mechanisms exists. One of the most effective measures for acute defense of the lung is the recruitment of neutrophils, which either phagocytose the inhaled pathogens or kill them by releasing cytotoxic chemicals. A recent addition to the arsenal of neutrophils is their explosive release of extracellular DNA-NETs by which bacteria or fungi can be caught or inactivated even after the NET releasing cells have died. We present here a method that allows one to directly observe neutrophils, migrating within a recently infected lung, phagocytosing fungal pathogens as well as visualize the extensive NETs that they have produced throughout the infected tissue. The method describes the preparation of thick viable lung slices 7 hours after intratracheal infection of mice with conidia of the mold Aspergillus fumigatus and their examination by multicolor time-lapse 2-photon microscopy. This approach allows one to directly investigate antifungal defense in native lung tissue and thus opens a new avenue for the detailed investigation of pulmonary immunity.